First record of Hylophasma Townes (Hymenoptera, Ichneumonidae, Cryptinae) from Palaearctic region - Wang, Xi-Nan; Li, Tao; Sheng, Mao-Ling (Zootaxa, 2019)
A new species of Cryptinae, Hylophasma luica Sheng, Li & Wang, sp.n., collected from Shandong Province, in the southern border of the Eastern Palaearctic Region of China, is described and illustrated. The new species is placed within the existing key to species.